The Effectiveness of a 2‐year Supplementary Tutor‐assisted Computerized Intervention on the Reading Development of Beginning Readers at Risk for Reading Difficulties: A Randomized Controlled Trial. (17th October 2013) - Regtvoort, Anne; Zijlstra, Haytske; van der, Aryan; van der, Aryan; Maassen, Ben
<x xml:space="preserve">Abstract</x> Children with low (pre‐)literacy skills may benefit from individual tutoring during the early phases of learning to read. Dutch at‐risk students from 13 schools received in first and second grade a computerized reading intervention, delivered by non‐professional tutors at school. Digital logs indicated that treatment integrity was lower than intended; therefore, the intervention group was subdivided using a completion criterion. Third grade assessments revealed that the subgroup that had finished the program successfully (IF, N = 40) was able to read as fluent as the average reader, outperforming the subgroup that had not completely finished the program (InF, N = 31) as well as the group that had not worked with the program (controls, N = 66) on all reading measures. This study demonstrates that a well‐implemented tutoring model can serve as a (cost‐)effective complement to the classroom practice for beginning readers. Copyright © 2013 John Wiley & Sons, Ltd.